Annual and semi-annual variations of electron density in the topside ionosphere observed by CSES - Zhu, Keying; Yan, Rui; Xiong, Chao; Zheng, Lin; Zhima, Zeren; Shen, Xuhui; Liu, Dapeng; Guan, Yibing; Liu, Chao; Xu, Song; Lv, Fangxian; Guo, Feng; et al. (Frontiers in Earth Science, 2023)
In this paper, based on the observations from Langmuir probe (LAP) onboard the China Seismo-Electromagnetic Satellite (CSES), the annual/semi-annual variations of electron density (Ne) measured at 02:00 and 14:00 local time (LT) in the topside ionosphere have been analyzed. Results indicated that the Ne exhibits an amplification-linear-saturation with the increase of P10.7 in the daytime, while roughly linear in the nighttime. The annual/semi-annual variations of CSES Ne at around 500 km are found by morphological analysis and Morlet wavelet analysis, with dominant period of 187 days and 374 days. The annual components of longitude-averaged Ne dominate at most magnetic latitudes (Mlats) with maxima around the June solstices in the northern hemisphere and the December solstice in the southern hemisphere (except for the northern hemisphere in the nighttime), while the semi-annual variation dominates at the magnetic equator and low magnetic latitudes with two maxima at equinoxes. The Ne dominant period is characterized by a transition from semi-annual variation at the equator and low magnetic latitudes regions to annual variation at the middle magnetic latitudes region. The annual/semi-annual variations of Ne observed by CSES satellite show a consistent performance with previous studies, and have complemented the ionospheric characteristics at 500 km altitude, especially in the nighttime.